Model and a solution algorithm for the dynamic resource allocation problem for large-scale transportation network evacuation - He, Xiaozheng; Zheng, Hong; Peeta, Srinivas (Transportation research. Part C, Emerging technologies, 2015)
•Develop an MILP model for the dynamic resource allocation problem.•Describe evacuation traffic dynamics using the earliest arrival flow formulation.•Reduce the combinatorial complexity by introducing auxiliary binary variables.•Apply Benders decomposition scheme to solve the problem efficiently. Allocating movable resources dynamically enables evacuation management agencies to improve evacuation system performance in both the spatial and temporal dimensions. This study proposes a mixed integer linear program (MILP) model to address the dynamic resource allocation problem for transportation evacuation planning on large-scale networks. The proposed model is built on the earliest arrival flow formulation that significantly reduces problem size. A set of binary variables, specifically, the beginning and the ending time of resource allocation at a location, enable a strong formulation with tight constraints. A solution algorithm is developed to solve for an optimal solution on large-scale network applications by adopting Benders decomposition. In this algorithm, the MILP model is decomposed into two sub-problems. The first sub-problem, called the restricted master problem, identifies a feasible dynamic resource allocation plan. The second sub-problem, called the auxiliary problem, models dynamic traffic assignment in the evacuation network given a resource allocation plan. A numerical study is performed on the Dallas–Fort Worth network. The results show that the Benders decomposition algorithm can solve an optimal solution efficiently on a large-scale network.